THE SOUTH AFRICAN NAVY AND ITS PREDECESSORS, 1910–2010: A CENTURY OF INTERACTION WITH COMMONWEALTH NAVIES - Wessels, André (Scientia Militaria - South African Journal of Military Studies, 2011)
In this article, the history of the South African Navy (SAN) and its predecessors is reviewed, as well as the interaction with other Commonwealth navies during the years 1910 to 2010. Although the Union Defence Forces were established in 1912, the Union only acquired its first naval force in 1922, when the South African Naval Service (SANS) was formed. In the meantime, the country’s naval defence was conducted by the Royal Navy (RN). During World War I, 164 members of the South African Division of the Royal Naval Volunteer Reserve served in the RN. The SANS’s three small ships were withdrawn from service in 1933 to 1934, and when World War II broke out, the country’s naval forces had to be built up from scratch – but soon played an important role in patrolling the Cape sea route (and also saw action in the Mediterranean). After the war, South Africa’s naval forces were rationalised, but – in the context of the Cold War and the Soviet threat to the Cape sea route – the SAN then gradually grew in size and importance, albeit that it was (and today still is) small in comparison to major Commonwealth navies. In 1957, the SAN acquired the RN’s Simon’s Town Naval Base. Many exercises were held with the RN and other navies, but gradually South Africa became more isolated internationally because of the National Party government’s racially-based policy of apartheid. In due course, this impacted negatively on the SAN and its interaction with other navies. In 1975, the Simon’s Town Agreement was abrogated and in 1977, the United Nations imposed a mandatory arms embargo against South Africa. In the meantime, the Republic of South Africa (RSA) became embroiled in the Namibian War of Independence (1966–1989) – a war that spilled over into Angola. The SAN played a small, albeit important, role in the war, but the conflict affected the navy negatively. The advent of the truly democratic RSA in 1994 opened new opportunities for the SAN, and since then, the SAN has undertaken many flag-showing cruises to several Commonwealth and other countries, while many foreign warships, including from Commonwealth navies, have visited the RSA and exercised with the SAN.